2015
DOI: 10.1007/s10773-015-2573-7
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Quantum Discord for Two-Qubit X States: The Error Bound to an Analytical Formula

Abstract: In this article, we investigate the error bound of quantum discord, obtained by the analytic formula of Ali et al.[Phys. Rev. A 81(2010)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…(43) and (44) are the same, the intermediate subdomain Q θ is absent and the quantum discord is given by analytical expressions. On the other hand, instead of rough conditions (34) and (35), the inequalities S cond (0) ≤ 0 and S cond (π/2) ≤ 0 define now the complete subdomains Q 0 and Q π/2 , respectively.…”
Section: Equations For the Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…(43) and (44) are the same, the intermediate subdomain Q θ is absent and the quantum discord is given by analytical expressions. On the other hand, instead of rough conditions (34) and (35), the inequalities S cond (0) ≤ 0 and S cond (π/2) ≤ 0 define now the complete subdomains Q 0 and Q π/2 , respectively.…”
Section: Equations For the Boundariesmentioning
confidence: 99%
“…There exists a statement that classical correlations of binary states are optimized via projective positive operator valued measurements (projective POVMs):[29][30][31][32][33][34]. See also[21,38].…”
mentioning
confidence: 99%
“…Beyond X-states, recent studies in this direction reveal that for a large majority of two-qubit states, an optimal measurement is among the eigenstates of σ x , σ y , and σ z , and very small errors persist for the states which do not minimize on the aforementioned sets [235,244,245]. Motivated by these observations and the error analysis for the X-states, QD has been considered for different restricted classes of measurements, and the general term, "constrained QD", has been used to identify them [246].…”
Section: A Qubit Systemsmentioning
confidence: 99%
“…This is supported by the argument of deterministic quantum computation with one-qubit (DQC1) [ 17 ]. Further, A. Datta et al [ 18 ] insisted that quantum discord [ 19 , 20 , 21 ] can contribute to DQC1. It has been shown that quantum discord can be related not only to quantum computation [ 22 , 23 ], but also to quantum protocols such as quantum state merging [ 24 ], remote state preparation [ 25 ], and assisted optimal state discrimination [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%